Perbedaan Kemampuan Drible Siswa Sekolah Dasar Putra Dan Putri - Samodra, Touvan Juni (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2023)
The ability to dribble is one of the skills needed to play basketball. Elementary school age, especially the lower grades (1,2, 3) can already be introduced to basic dribbling movements and techniques. Between boys and girls at the age of the lower classes should have the same abilities if they get the same opportunity to learn motion. The purpose of this study was to reveal differences in the dribbling ability of elementary school students. The samples were elementary school students grades 1 to 3 in SDN 10 Anjungan elemantery school. With a total of 52 male and 65 female students. The instrument used was a zigzag dribbling ability test by recording the speed of completing drible assignments. Data were analyzed with no parametric statistics. The results showed that there was no difference in the ability to dribble in male and female elementary school students